Seasonal energy performance evaluation with new perspective on partial-coupling ejection-compression solar cooling system for modern city buildings. (1st April 2021) - Xu, Yingjie; Shi, Qiqi; Chen, Ning; Shen, Xi; Wang, Chunyan; Han, Xiaohong
Highlights: New solar cooling cycle for modern city building is optimized and analyzed hourly. New cycle has best electric efficiency over 6.2 for high building in city. Solar factor and thermal efficiency of new cycle in 6-floor building near 1 and 3.4. New cycle consumes 1/3 primary energy of existing one, suitable for high buildings. Abstract: Space cooling accounts for high percentage of energy consumption in modern city building. To improve energy utilizing efficient of space cooling, a new system based on solar partial-coupling ejection-compression refrigeration cycle is studied. Builds are assumed to be located at modern city of Shanghai, with area of 100 m 2 for each floor. With a model combining cooling system, building, and weather information, comparative analysis is carried out hourly, using new perspective of total primary energy, during the whole cooling season. For the building with a common height of six-storey in modern city, partial-coupling ejection-compression refrigeration cycle reveals obvious superiority in electric coefficient of performance, solar factor, thermal coefficient of performance, total primary energy, with best value of 6.2, 1, 3.6, and 14 kW, respectively, which helps to reduce carbon dioxide emission. The remarkable difference in auxiliary heat between partial-coupling ejection-compression refrigeration cycle and traditional ejection-compression refrigeration cycle results in the great primary energy saving of partial-coupling cycle, which reveals significant superiority and good suitability of partial-coupling cycle used in multi-stroey buildings in modern city.